Art and Religiosity in the Aesthetic-Philosophical System of Dmitry Sergeyevich Merezhkovsky - Vorel, Jan (Poznańskie Studia Slawistyczne, 2015)
The study is aimed on traces of religiosity in aesthetic-philosophical system of a Russian symbolistic poet, prosaic writer and thinker D.S. Merezhkovsky. The study analyses selected Merezhkovsky’s works with focus on aesthetics, his essays, historiosophic prose and philosophic religious treatises. For Russian spiritual and art culture, importance of Merezhovsky is obvious, especially in connection with his effort to overcome crisis processes in religious, philosophical and art sphere, realized by means of synthesis and transcendence in modern culture.